1 + 1 + x 1 + 1 + x 1 = x + x 1
Which of the following is the root of the above equation?
Note: ϕ = 2 5 + 1 and denotes the golden ratio .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Golden solution... + ( ϕ 2 − ϕ ) .....
PS:Correct the typo where you have found x.. You forgot to add a minus sign- 2 − 1 ± 5 .
Problem Loading...
Note Loading...
Set Loading...
We have 1 + 1 + x 1 + 1 + x 1 = x + 1 x + 2 + 1 = x ( x + 2 + 1 ) = x ( x + 3 + 2 x + 2 ) = x 2 + 3 x + 2 x x + 2 = x 3 + 2 x 2 − 2 x x + 2 + 1 = ( x x + 2 ) 2 − 2 x x + 2 + 1 = ( x x + 2 − 1 ) 2 = x x + 2 = x 2 ( x + 2 ) = x 3 + 2 x 2 − 1 = ( x + 1 ) ( x 2 + x − 1 ) = x = = x + x 1 x x + 1 ( x + 1 ) x + 1 ( x + 1 ) 3 x 3 + 3 x 2 + 3 x + 1 0 0 0 1 1 0 0 − 1 , 2 − 1 ± 1 + 4 − 1 , 2 − 1 ± 5 [ simplifying ] [ ∵ ( x + 1 ) x + 1 = ( x + 1 ) 2 3 ] But notice that − 1 , 2 − 1 − 5 do not satisfy the above equation. ∴ x = = 2 5 − 1 ϕ − 1